Utformning av en elbilsbatterisimulator för en säker och effektiv lärandesituation - Axelsson, Josefin; Lundgren, Joel (My University)
here is a lack of technicians in the fast-growing electric vehicle market of today. Furthermore, the technician's first interaction with a battery is in a high-voltage environment. In this thesis, a physical product is designed to simulate an electric vehicle battery. This ensures a safe and effective learning environment for training technicians. To uphold this, the product is to achieve the perception of a substantial scenario. By studying technicians performing the scenarios and completing a literature study of the functioning components the requirements were defined for the product and its components. Thereafter key components were identified and selected as well as their arrangements and functions. The simulator is designed to allow the technician to practice their actions on welded contactors, loss of isolation and broken fuses. Demounting of the Manual Service Disconnect (MSD) and battery case are also included as well as a simulation to control the functionality of the battery. Together with the layout of the product, the scenarios are achieved by using specific measurements of voltages and relays, with a specified service procedure for each scenario. The concept divides the functioning of the company-provided electronic solution from the visible battery from the technician. Furthermore, the layout features a framing of the battery, selectively showing the technician the most important components in an arrangement that communicates the continuous modules of the battery. The electric vehicle market is under a fast development which could impact the solutions made through the project. However, the product is modular and could easily upgrade an individual component as well as a larger amount of components to fit the current market need
Keywords: EV-battery; training simulator; EV-battery components; practical simulation; service scenarios